Modeling and Control of an Aeropendulum System Using a Takagi-Sugeno Fuzzy Controller - Acosta-Barbosa, K; El Aiss-Berazouq, H (Institute of Electrical and Electronics Engineers Inc., 2024)
This paper addresses the control problem of Aeropendulum systems. The Aeropendulum, known for its nonlinear dynamics, will be approximated as a Takagi-Sugeno (T-S) fuzzy system by introducing a new state variable. A Parallel Distributed Compensation (PDC) controller will be employed to control the derived T-S fuzzy model, which will then be applied to the nonlinear system. Using the Lyapunov function and incorporating slack matrices, a stabilization condition will be established in a set of Linear Matrix Inequalities (LMIs). The performance of the proposed controller will be compared with both a Linear Quadratic Regulator (LQR) and a state feedback control. Finally, simulation results, utilizing Aeropendulum parameters, will demonstrate the effectiveness and validity of the proposed technique. © 2024 IEEE.